Sensitivity of a Simulated Squall Line During Southern China Monsoon Rainfall Experiment to Parameterization of Microphysics. Issue 8 (21st April 2018) - Qian, Qifeng; Lin, Yanluan; Luo, Yali; Zhao, Xi; Zhao, Zongci; Luo, Yong; Liu, Xi
Abstract: A squall line on 22 May 2014 during the Southern China Monsoon Rainfall Experiment period is simulated with four bulk microphysical parameterizations (BMPs) using the Weather Research and Forecasting (WRF) model. Although most BMPs are able to capture the basic features of the squall line, the movement, morphology, and especially the length of the simulated squall lines differ significantly among BMPs. Morrison scheme tends to simulate a slower moving squall line with a weaker cold pool and better trailing stratiform cloud and precipitation due to the smaller snow fall speed and faster generation of snow particles than other schemes. Assuming hail or graupel in different schemes could result in different melting profiles of rimed‐ice particles, with hail melted substantially below the 0°C isotherm and contributing to the cold pool production significantly in WRF double‐moment six‐class microphysics scheme because of its use of larger fall speed for hail. Although ice‐phase particles simulated differ significantly among BMPs, it is rain evaporation that dominates the cold pool generation and maintenance of the squall line in this case. Stronger rain evaporation generally contributes to stronger cold pools and thus faster movement and longer simulated squall lines. Failure of the Stony Brook University‐YLin scheme in capturing the squall line was identified to be related to the turnoff of rain evaporation once environmental relative humidity is larger than 90%. With modifications of rain evaporation calculation and saturation adjustment method, the scheme is able to simulate this squall line reasonably well. Key Points: Simulated squall line length is mainly controlled by the cold pool intensity, which is mainly regulated by rain evaporation SBU‐YLIN microphysics scheme is improved by modified rain evaporation and saturation adjustment